Hypercrosslinked conjugated microporous polymers for carbon capture and energy storage. (26th April 2017) - Jiang, Xiaowei; Liu, Yunfei; Liu, Jun; Fu, Xiaohui; Luo, Yali; Lyu, Yinong
Abstract : Three monomers with different geometrical configurations were employed to synthesize hypercrosslinked conjugated microporous polymers via Friedel–Crafts alkylation reaction. Abstract : Three hypercrosslinked conjugated microporous polymers were prepared using Friedel–Crafts reaction based on tetraphenylporphyrin, triphenylamine and tetraphenylmethane with p -dimethoxybenzene as an external crosslinker. The polymers show large surface areas (921 m 2 g −1 ) and CO2 uptake capacity (12.3 wt%). Due to its π-conjugated structure, the tetraphenylporphyrin based polymer (HCTPP) shows high specific capacitance (179 F g −1 ). Considering their large surface area, high gas uptake capacity, good specific capacitance and facile synthesis method, these materials are promising candidates for carbon capture and energy storage.